Spontaneous Atypical Intracerebral Hematoma in a Patient with Metastatic Colon Cancer using Bevacizumab without Central Nervous System Metastases - Silva, Guilherme Gago da; Pizzol, Antonio Dal, Junior; Santos, Alexei Peter dos; Britz, João Pedro Einsfeld; Worm, Paulo Valdeci (Brazilian Journal of Oncology, 2021)
We report a case of a patient with metastatic colon cancer without central nervous system metastases who presented with a spontaneous intraparenchymal hematoma using bevacizumab, without coagulation disorders or metastatic cells in the pathological examination. Bevacizumab is amonoclonal antibody against vascular endothelial growth factor (VEGF) that inhibits binding of the normal VEGF ligand to its receptor and is used to treat various tumors. Its therapeutic effect is believed to occur by limiting the formation of new blood vessels in tumors and decreasing their oxygenation. Fatal cerebrovascular events have been reported with the use of bevacizumab, raising the discussion of the safety of its use, especially in patients with brain metastases. At present, controversial remains as to bevacizumab increases the risk of cerebrovascular events.
Keywords: Bevacizumab; Cerebral hemorrhage; Neurosurgery; Intracranial hemorrhages; Antineoplastic agents.